Structural and Geomorphic Evidence for Rolling‐Hinge Style Deformation of an Active Continental Low‐Angle Normal Fault, SE Papua New Guinea. Issue 5 (6th May 2019) - Mizera, M.; Little, T. A.; Biemiller, J.; Ellis, S.; Webber, S.; Norton, K. P.
Abstract: To what degree low‐angle normal faults (LANFs) deform by a "rolling‐hinge" mechanism is still debated for continental metamorphic core complexes (MCCs). The Mai'iu fault in SE Papua New Guinea is one of the best preserved and fastest slipping active continental LANFs on Earth, providing an ideal setting in which to evaluate footwall deformation and doming in MCCs. We analyzed structural field data from the exhumed slip surface and subjacent footwall of the Mai'iu fault, together with geomorphic data interpreted from aerial photographs and GeoSAR‐derived digital terrain models. The exhumed part of the Mai'iu fault forms a smooth, continuous surface, traced at least 28 km in the slip direction. The fault emerges from the ground near sea level with a northward dip of ≤22°N and flattens southward over the crest of the Suckling‐Dayman Dome. Its most southern mapped portion dips ~12°S. Geomorphic and structural evidence indicates updip tectonic transport of the footwall and progressive back‐tilting of the exposed part of the fault and the underlying foliation through >26°. We infer that antithetic (northside‐up) dip slip on an array of steep‐dipping faults striking parallel to the Mai'iu fault accommodated some of the exhumation‐related inelastic bending of the footwall. The exhuming footwall was subject to late‐stage slip‐parallel contractional strain as recorded by a postmetamorphic crenulation foliation that strikes parallel to the curved Mai'iu fault trace, by folds of bedding in a large rider block that is stranded on the current footwall and by strike‐parallel warps in the exhumed fault surface. Geodynamic modeling predicts the observed footwall strain. Key Points: We study an active, fast‐slipping low‐angle normal fault to evaluate deformational processes accommodating slip and bending on this fault Tectonic‐geomorphic data suggest that the Mai'iu fault evolves by the rolling‐hinge mechanism from original dips ≥40°N Antithetic faults resulting from bending stresses provide the first clear example of footwall deformation accommodating a rolling hinge